Intrusive memory frequency and related inner tension following dialectical behavior therapy or cognitive processing therapy for posttraumatic stress disorder: an e-diary study - Schmitz, Sara Elena; Ebner-Priemer, Ulrich W.; Kleindienst, Nikolaus; Friedmann, Franziska; Bohus, Martin; Steil, Regina; Müller-Engelmann, Meike; Limberger, Matthias F.; Hartnagel, Lisa-Marie; Santangelo, Philip; Priebe, Kathlen (JMIR mental health, 2025)
Background: Intrusive memories are a core symptom of posttraumatic stress disorder (PTSD), yet their retrospective assessment is prone to biases, making real-time methods such as e-diaries essential. While trauma-focused treatments target intrusive symptoms, their efficacy has not yet been evaluated using real-time assessments. Objective: We aimed to use e-diaries to assess and compare the effects of dialectical behavior therapy for PTSD (DBT-PTSD) and cognitive processing therapy (CPT) on intrusive memories and related inner tension in a large sample of PTSD patients. Methods: In a multicenter randomized controlled trial (RCT; German Clinical Trials registration number: DRKS00005578), 193 women with PTSD related to childhood sexual or physical abuse were randomized to receive either DBT-PTSD or CPT. E-diary assessments were conducted at three time points: before treatment, after six months, and after twelve months of therapy. At each time point, participants reported intrusive memories and related inner tension over five consecutive days using an event-based design. Results: Both intrusive memories and related inner tension decreased significantly over time (intrusions: ß = -.53, P<.001; inner tension: ß = -.15, P<.001). While reductions in intrusion frequency did not differ significantly between treatment groups (ß = .05, P=.45), DBT-PTSD was associated with significantly greater reductions in intrusion-related inner tension compared to CPT (ß = -.16, P<.001). Conclusions: This study provides the first real-time evaluation of trauma-focused PTSD treatments using e-diaries in daily life. Both interventions were associated with reduced intrusion frequency, while DBT-PTSD showed greater reductions in associated emotional distress, potentially reflecting its emphasis on emotion regulation strategies and repeated imaginal exposure. These findings highlight the value of e-diaries for capturing treatment-related symptom change in ecologically valid contexts. Clinical Trial: Participants of this study were recruited as part of a multicenter RCT (German Clinical Trials registration number: DRKS00005578), titled “Treating Psychosocial and Neural Consequences of Childhood Interpersonal Violence in Adults”.